One Year Mortality of Patients Treated with Naloxone for Opioid Overdose by Emergency Medical Services - Weiner, Scott G. (Subst Abus, 2022)
STUDY OBJECTIVE: Prehospital use of naloxone for presumed opioid overdose has increased markedly in recent years because of the current opioid overdose epidemic. In this study, we determine the one-year mortality of suspected opioid overdose patients who were treated with naloxone by EMS and initially survived. METHODS: This was a retrospective observational study of patients using three linked statewide datasets in Massachusetts: emergency medical services (EMS), a master demographics file, and death records. We included all suspected opioid overdose patients who were treated with naloxone by EMS. The primary outcome measures were death within 3 days of treatment and between 4 days and 1 year of treatment. RESULTS: Between July 1, 2013 and December 31, 2015, there were 9,734 individuals who met inclusion criteria and were included for analysis. Of these, 807 (8.3% (95% confidence interval (CI) 7.7%-8.8%)) died in the first 3 days, 668 (6.9% (95% CI 6.4%-7.4%)) died between 4 days and 1 year, and 8,259 (84.8% (95% CI 84.1%-85.6%)) were still alive at one year. Excluding those who died within 3 days, 668 of the remaining 8,927 individuals (7.5% (95% CI 6.9%-8.0%)) died within one year. CONCLUSION: The one-year mortality of those who are treated with naloxone for opioid overdose by EMS is high. Communities should focus both on primary prevention and interventions for this patient population, including strengthening regional treatment centers and expanding access to medication for opioid use disorder.